2020
DOI: 10.3390/ijms22010324
|View full text |Cite
|
Sign up to set email alerts
|

Shiftwork and Light at Night Negatively Impact Molecular and Endocrine Timekeeping in the Female Reproductive Axis in Humans and Rodents

Abstract: Shiftwork, including work that takes place at night (nightshift) and/or rotates between day and nightshifts, plays an important role in our society, but is associated with decreased health, including reproductive dysfunction. One key factor in shiftwork, exposure to light at night, has been identified as a likely contributor to the underlying health risks associated with shiftwork. Light at night disrupts the behavioral and molecular circadian timekeeping system, which is important for coordinated timing of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 187 publications
(302 reference statements)
0
10
0
Order By: Relevance
“…Sleep disturbances in shift workers cause reduced melatonin production and excessive activation of the hypothalamic-pituitary-adrenal (HPA) axis, resulting in early loss of pregnancies, failed embryo implantation, or lack of ovulation. Lack of sleep in women also affects the secretion of gonadotropins and sex steroids, which leads to infertility in women [19,[23][24][25][26][27]. Our research has shown that reproductive problems, such as the failure to get pregnant for more than six months, miscarriage (also recurrent), and congenital fetal anomalies occurred in 23.7% of midwives working nights and only in 7.6% of midwives working days only.…”
Section: Discussionmentioning
confidence: 81%
“…Sleep disturbances in shift workers cause reduced melatonin production and excessive activation of the hypothalamic-pituitary-adrenal (HPA) axis, resulting in early loss of pregnancies, failed embryo implantation, or lack of ovulation. Lack of sleep in women also affects the secretion of gonadotropins and sex steroids, which leads to infertility in women [19,[23][24][25][26][27]. Our research has shown that reproductive problems, such as the failure to get pregnant for more than six months, miscarriage (also recurrent), and congenital fetal anomalies occurred in 23.7% of midwives working nights and only in 7.6% of midwives working days only.…”
Section: Discussionmentioning
confidence: 81%
“…Clock genes are important in homeostatic regulation of cells and provide a molecular mechanism allowing tissues to anticipate daily changes in physiological functions. Despite the well-established role of circadian rhythms and clock genes in female reproductive function and pregnancy maintenance 37 , 39 , 42 , 43 , 69 , our understanding of the contribution of clock genes in placental development and function in relation to PE is in its infancy. Here, we find that among the 17 clock genes analyzed, only CRY1 , NR1D2 and PER3 are consistently up- ( CRY1 ) and down- ( NR1D2 and PER3 ) regulated in the PE placenta, independent of PE subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the core circadian transcriptional regulators are: Aryl hydrocarbon receptor nuclear translocator-like protein 1 (ARNTL1, also known as BMAL1), Circadian Locomotor Output Cycles Kaput (CLOCK), Period 1/2/3 (PER1/2/3), Cryptochrome 1/2 (CRY1/2) and the nuclear receptor subfamily 1 group D members 1/2 (NR1D1/2, also known as REV-ERBα/β). Circadian clock genes are expressed in female reproductive tissues, such as the ovary, oviducts, uterus, and placenta 33 , 37 42 . While the role of circadian genes in the ovary is well-understood 43 , their role in the placenta remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important key factor in regulating female fertility and pregnancy. During pregnancy, melatonin reduces oxidative stress and protects the baby from undergoing any harm by the ROS ( Nakamura et al, 2001 ; Tamura et al, 2008 ; Yaw et al, 2021 ).…”
Section: Circadian Rhythm and Physiological Functionsmentioning
confidence: 99%